Design of X-band wideband dual circularly polarized microstrip array antenna for satellite communication system - Sui Tao; Xing Sirui; Jin Yuting; An Xiangdong (Dianzi Jishu Yingyong)
A novel X-band wideband dual-circularly polarized microstrip array antenna is designed to meet the requirements of a satellite X-band communication data forwarding system. The antenna unit adopts microstrip form, the overall energy feed mode is bottom feed, the slot-coupling feed mode is adopted to achieve wide band, and the 3 dB directional coupler is adopted to realize the phase difference between the two signals to meet the dual circularly polarization. The array antenna consists of 24 antenna units arranged in a 4×6 rectangle, each of which is rotated in a group of 4 units. Through the analysis of electromagnetic simulation software, it can be obtained that the array antenna has a gain of 17.9 dBi and an axis ratio of 0.06 dB at the center frequency of 8.2 GHz in the operating frequency band of 8 GHz~8.4 GHz. The antenna achieves the performance indexes such as wide band and double circularly polarization, and has certain guiding significance for the design of X-band wireless communication system.